Development and validation of an early childhood development scale for use in low-resourced settings. Issue 1 (December 2017) - McCoy, Dana; Sudfeld, Christopher; Bellinger, David; Muhihi, Alfa; Ashery, Geofrey; Weary, Taylor; Fawzi, Wafaie; Fink, Günther
Abstract Background Low-cost, cross-culturally comparable measures of the motor, cognitive, and socioemotional skills of children under 3 years remain scarce. In the present paper, we aim to develop a new caregiver-reported early childhood development (ECD) scale designed to be implemented as part of household surveys in low-resourced settings. Methods We evaluate the acceptability, test-retest reliability, internal consistency, and discriminant validity of the new ECD items, subscales, and full scale in a sample of 2481 18- to 36-month-old children from peri-urban and rural Tanzania. We also compare total and subscale scores with performance on the Bayley Scales of Infant Development (BSID-III) in a subsample of 1036 children. Qualitative interviews from 10 mothers and 10 field workers are used to inform quantitative data. Results Adequate levels of acceptability and internal consistency were found for the new scale and its motor, cognitive, and socioemotional subscales. Correlations between the new scale and the BSID-III were high (r > .50) for the motor and cognitive subscales, but low (r < .20) for the socioemotional subscale. The new scale discriminated between children's skills based on age, stunting status, caregiver-reported disability, and adult stimulation. Test-retest reliability scores were variable among a subset of items tested. Conclusions Results of this study provide empirical support from a low-income country setting for the acceptability, reliability, and validity of a new caregiver-reported ECD scale. Additional research is needed to test these and other caregiver reported items in children in the full 0 to 3 year range across multiple cultural and linguistic settings.